Country report for ALO Meeting at IRETA,Samoa, 12-14 August, 2002 - Agriculture Liaison Officer Meeting, (2002 : Samoa); Maniha, Nicks Sasingian (Papua New Guinea : Department of Agriculture and Livestock, 2002)
"This brief paper highlights the functions and responsibilities of the National Department of Agriculture and Livestock (NDAL) in Papua New Guinea. The paper highlights current programs and resource summaries, set against what is conceived under the National Agriculture Development Strategy, Horizon 2001-2012 (NADSH) and the recent Medium Term Development Strategy (MTDS) to reform the agriculture sector to contribute to the national economy over the next five to ten years"--Leaf 1.
Part A: summary of the National Department of Agriculture and Livestock functions and activities -- Part B: medium term development strategy - for reforming the agriculture sector 2003-2007.
Keywords: Papua New Guinea. -- National Department of Agriculture and Livestock; Agriculture and state -- Papua New Guinea; Agriculture -- Papua New Guinea